The hidden harm of home-based care: pulmonary tuberculosis symptoms among children providing home medical care to HIV/AIDS-affected adults in South Africa. - Cluver, L; Orkin, M; Moshabela, M; Kuo, C; Boyes, M (2013)
Millions of children in sub-Saharan Africa undertake personal and medical care for family members who are unwell with AIDS. To date, no research has investigated whether such care provision places children at heightened risk for pulmonary tuberculosis. This study aimed to address this gap by identifying risk factors for paediatric pulmonary tuberculosis symptomatology. In 2009-2011, 6002 children aged 10-17 years were surveyed using door-to-door household sampling of census enumeration areas. These were randomly sampled from six urban and rural sites with over 30% HIV prevalence, within South Africa's three highest tuberculosis-burden provinces. Validated scales and clinical tuberculosis symptom checklists were modelled in multivariate logistic regressions, controlling for socio-demographic co-factors. Findings showed that, among children, severe pulmonary tuberculosis symptomatology was predicted by primary caregiver HIV/AIDS-illness [odds ratio (OR): 1.63, confidence interval (CI): 1.23-2.15, p<0.001], and AIDS-orphanhood (OR: 1.44, CI: 1.04-2.00, p<0.029). Three-fold increases in severe tuberculosis symptoms were predicted by the child's exposure to body fluids through providing personal or medical care to an ill adult (OR: 3.12, CI: 1.96-4.95, p<0.001). Symptoms were also predicted by socio-economic factors of food insecurity (OR: 1.52, CI: 1.15-2.02, p<0.003) and household overcrowding (OR: 1.35, CI: 1.06-1.72, p<0.017). Percentage probability of severe tuberculosis symptoms rose from 1.4% amongst least-exposed children, to 18.1% amongst those exposed to all above-stated risk factors, independent of biological relationship of primary caregiver-child and other socio-demographics. Amongst symptomatic children, 75% had never been tested for tuberculosis. These findings identify the risk of tuberculosis among children providing home medical care to their unwell caregivers, and suggest that there are gaps in the health system to screen and detect these cases of paediatric tuberculosis. There is a need for effective interventions to reduce childhood risk, as well as further support for community-based contact-tracing, tuberculosis screening and anti-tuberculosis treatment for children caring for ill adults in contexts with a high burden of HIV and tuberculosis.